Assess the Typhoon-driven Extreme Wave Conditions in Manila Bay through Numerical Simulation and Statistical Analysis. (April 2021) - Sun, Yabin; Wang, Kehua; Zhong, Xionghua; Zhou, Zhipeng; Ren, Zhaofei; Zhang, Jun
Highlights: This study systematically demonstrates a general procedure of deriving the design wave parameters for an engineering project using both numerical modelling and statistical analysis, in consideration of the typhoon-induced extreme storm waves. This study simulates the storm waves of the 36 typhoons events in Manila Bay using a third-generation spectral wave model with a nested wave modelling scheme. The model outputs are validated by the Jason-2 altimetry wave heights, which shows the Hybrid wind field produces more accurate wave simulation results as compared to the JTWC and CFSR wind. Moment ratio diagram: Kurtosis coefficient Ck vs. Skewness coefficient Cs is used to select the best distribution functions in the extreme value analysis, which is carried out to determine the extreme wave conditions at the project locations corresponding to different return periods. The proposed procedure can be applied to any actual coastal, near-shore and ocean projects of similar type, and is of great value for the engineering design practice. Abstract: Philippines is the most exposed country in the world to typhoons, with an average of twenty tropical cyclones entering the Philippine Area yearly. This study develops numerical models to simulate the extreme waves driven by typhoons, in an attempt to provide design wave conditions for a hypothetical land reclamation project in Manila Bay. A total number of 36 tropical storms passing through Manila Bay are selected within a 200 km search radius of the project for the period from 1977 to 2016. The typhoon-driven storm waves in Manila Bay are then simulated using a third-generation spectral wave model, driven by a hybrid wind field which combines both the typhoon information from JTWC (Joint Typhoon Warning Center) and the background information from CFSR (Climate Forecast System Reanalysis). A nested wave modelling scheme is adopted, which comprises of a regional wave model and a local wave model. The regional wave model encompasses all the typhoon tracks of the selected tropical storms, providing the wave inputs (spectrum) at the boundaries for the local wave model which covers the Manila Bay with a focus on the project locations. Model results of the maximum significant wave heights Hm0, the associated mean energy wave period Tm-1, 0, and wave direction at the project locations are extracted from the numerical simulation. Extreme value analysis is finally conducted, using the moment ratio diagram to select the best distribution functions, to determine the extreme wave conditions corresponding to different return periods.